Higher Lead and Lower Calcium Levels Are Associated with Increased Risk of Mortality in Malaysian Older Population : Findings from the LRGS-TUA Longitudinal Study - Theng, Choon Ooi; Devinder Kaur, Ajit Singh; Suzana, Shahar; Razinah, Sharif; Nurul Fatin, Malek Rivan; Asheila, Meramat; Nor Fadilah, Rajab (MDPI, 2023)
The main objective of this study is to determine the association of various trace elements’ status with the 5-year mortality rate among community-dwelling older adults in Malaysia. This study was part of the Long-term Research Grant Scheme—Towards Useful Ageing (LRGS-TUA). The participants were followed up for five years, and their mortality status was identified through the Mortality Data Matching Service provided by the National Registration Department, Malaysia. Of the 303 participants included in this study, 34 (11.2%) participants had died within five years after baseline data collection. As compared t o the survivors, participants who died earlier were more likely (p < 0.05) to be men, smokers, have a lower intake of total dietary fiber and molybdenum, higher intake of manganese, lower zinc levels in toenail samples, lower calcium and higher lead levels in hair samples during baseline. Following the multivariate Cox proportional hazard analysis, lower total dietary fiber intake (HR: 0.681; 0.532–0.871), lower calcium (HR: 0.999; 95% CI: 0.999–1.000) and higher lead (HR: 1.309; 95% CI: 1.061–1.616) levels in hair samples appeared as the predictors of mortality. In conclusion, higher lead and lower calcium levels are associated with higher risk of mortality among community-dwelling older adults in Malaysia. Our current findings provide a better understanding of how the trace elements’ status may affect older populations’ well-being and mortality rate.